2018
DOI: 10.1002/fuce.201700209
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Pre‐conditioning Process of Electrospun Nanofiber Electrodes in Polymer Electrolyte Fuel Cells

Abstract: Structure innovation and optimization of polymer electrolyte fuel cell (PEFC) catalyst layers is instrumental in improving catalyst utilization and effectiveness. Electrospinning technique has been recently used to fabricate nanofiber electrodes for PEFCs with improved performance compared to electrosprayed electrodes. However, the origins for the performance improvement are yet poorly understood. This study examined the evolution of the electrochemically active surface area (ECSA) and electrochemical impedanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…58 Moreover, experiments demonstrated a higher ECSA and performance for the layered fiber arrangement CL than the random particle stacking CL, especially at ultralow Pt loading. [60][61][62][63] For example, the MEA with the former showed approximately 20% larger power density than that with the latter at a low Pt loading of 0.1 mg Pt cm À2 . 60 The pores in the layered fiber arrangement CL can be divided into two types: one is formed by the catalyst/support agglomerations inside the fibers and the other is formed by the fibers that cross each other.…”
Section: Design Of Catalyst Layer Architecturementioning
confidence: 97%
See 1 more Smart Citation
“…58 Moreover, experiments demonstrated a higher ECSA and performance for the layered fiber arrangement CL than the random particle stacking CL, especially at ultralow Pt loading. [60][61][62][63] For example, the MEA with the former showed approximately 20% larger power density than that with the latter at a low Pt loading of 0.1 mg Pt cm À2 . 60 The pores in the layered fiber arrangement CL can be divided into two types: one is formed by the catalyst/support agglomerations inside the fibers and the other is formed by the fibers that cross each other.…”
Section: Design Of Catalyst Layer Architecturementioning
confidence: 97%
“…58 Moreover, experiments demonstrated a higher ECSA and performance for the layered fiber arrangement CL than the random particle stacking CL, especially at ultralow Pt loading. 60–63 For example, the MEA with the former showed approximately 20% larger power density than that with the latter at a low Pt loading of 0.1 mg Pt cm −2 . 60…”
Section: How To Design Catalyst Layers For Ultralow Pt Loading Pemfcsmentioning
confidence: 98%
“…Polyacrylic acid (PAA) is one of the commonly used carrier polymers for the fabrication of nanofiber fuel-cell catalyst layers for a variety of catalyst systems. ,,, Previous studies have identified the optimal concentration of PAA in the inks to produce uniform fiber morphologies . Researchers have also reported on the impact of PAA on performance, though at limited PAA concentrations (10–15 wt % PAA with respect to (w.r.t) total solids, i.e., Nafion, PAA, and particles). , Excessive PAA was found to reduce fuel cell performance by decreasing the ionic and electronic conductivity of the electrode. , However, systematic studies investigating how the concentration of PAA affects both the evolution of the fiber morphologies and the performance are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…2 Polyacrylic acid (PAA) is one of the commonly used carrier polymers for the fabrication of nanofiber fuel-cell catalyst layers for a variety of catalyst systems. 7,21,26,27 Previous studies have identified the optimal concentration of PAA in the inks to produce uniform fiber morphologies. 25 Researchers have also reported on the impact of PAA on performance, though at limited PAA concentrations (10−15 wt % PAA with respect to (w.r.t) total solids, i.e., Nafion, PAA, and particles).…”
Section: ■ Introductionmentioning
confidence: 99%
“…To improve polymer electrolyte fuel cell (PEFC) performance and increase durability, the catalysts and membranes have been developed (1,2,3) and the CCL structures have been investigated (4,5,6). There are a lot of operating conditions which control the PEFC performance as well.…”
Section: Introductionmentioning
confidence: 99%